Prospects for a Rim County Renaissance: Pandemic as Economic Opportunity - Vail, David (Maine Policy Review, 2021)
In previous Maine Policy Review essays, the author assessed the chronic economic distress facing Maine’s rim counties. His forecast for “more of the same” has been largely borne out by facts on the ground. At the end of 2021, however, he foresees new opportunities in the coming decade, based on a mix of positive external forces and creative Maine responses. Their economic potential is also strengthened by a massive infusion of federal dollars, the spread of high-speed telecommunications, and even the climate crisis. With critical state support, private-public-nonprofit partnerships are re-inventing rural Maine’s heritage industries—forest products, the food system, and tourism—and tapping its renewable energy potential. Pursued together, these silver buckshot initiatives can move many rim county communities onto a sustainable development path.